Neuropsychiatric implications of transient receptor potential vanilloid (TRPV) channels in the reward system. (December 2019) - Singh, Raghunath; Bansal, Yashika; Parhar, Ishwar; Kuhad, Anurag; Soga, Tomoko
Abstract: Neuropsychiatric disorders (NPDs) exert a devastating impact on an individual's personal and social well-being, encompassing various conditions and brain anomalies that influence affect, cognition, and behavior. Because the pathophysiology of NPDs is multifactorial, the precise mechanisms underlying the development of such disorders remain unclear, representing a unique challenge in current neuropsychopharmacotherapy. Transient receptor potential vanilloid (TRPV) type channels are a family of ligand-gated ion channels that mainly include sensory receptors that respond to thermal, mechanical and chemical stimuli. TRPV channels are abundantly present in dopaminergic neurons, thus playing a pivotal role in the modulation of the reward system and in pathophysiology of diseases such as stress, anxiety, depression, schizophrenia, neurodegenerative disorders and substance abuse/addiction. Recent evidence has highlighted TRPV channels as potential targets for understanding modulation of the reward system and various forms of addiction (opioids, cocaine, amphetamines, alcohol, nicotine, cannabis). In this review, we discuss the distribution, physiological roles, ligands and therapeutic importance of TRPV channels with regard to NPDs and addiction biology. Highlights: Neuropsychiatric disorders (NPDs) and drug-abuse have a global socioeconomic burden. TRPV channels are distributed abundantly in CNS. TRPV channels are in involved in many forms of addiction and NPDs. TRPV modulation need to be explored for novel therapeutics in NPDs and addiction.